Article of the week - Gallagher, Kelly; Power, Brenda; Choice Literacy Productions; Stenhouse Publishers (Portland : Stenhouse Publishers, 2009)
Teacher Kelly Gallagher developed'Article of the Week' to address serious gaps in his high school students' knowledge. In this video, he shows teachers how to integrate'Article of the Week' into their own classrooms to provide the background knowledge that is the foundation of critical reading
Cameras, Michael Boucher, James Whitney ; editor, Michael Boucher ; music, Steven Hansen
Instructor: Kelly Gallagher
DVD format
Keywords: Reading (Secondary); Critical thinking -- Study and teaching (Secondary)